2020
DOI: 10.3389/fped.2020.00257
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Necrotizing Enterocolitis in Preterm Patients With and Without Persistent Ductus Arteriosus and in Patients With Congenital Heart Disease

Abstract: Background: Diagnosis and management of NEC is based on clinical, radiological, and laboratory findings. Discrimination of pathogens for an improved understanding of NEC in preterm infants and NEC in infants with congenital heart disease has been previously discussed and enables evaluation of further NEC biomarkers. Patients and Methods: Within a study period of 11 years (2008-2019), we identified 107 patients with a diagnosis of NEC at our primary care center. Thirty-six out of 54 patients suffering from NEC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 29 publications
(36 reference statements)
2
15
0
Order By: Relevance
“…NEC develops in response to an abnormal interaction of exaggerated bacterial signaling in the premature intestine [ 4 ], in which E. coli plays a major role. The results of our study confirm an association of positive intraabdominal swabs and the presence of CHD/PDA, as demonstrated in a recent study [ 11 ] and show a predominance of E. coli and Staphylococcus in intraabdominal swabs. DMBT1 addresses a critical factor in the pathogenesis of NEC.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…NEC develops in response to an abnormal interaction of exaggerated bacterial signaling in the premature intestine [ 4 ], in which E. coli plays a major role. The results of our study confirm an association of positive intraabdominal swabs and the presence of CHD/PDA, as demonstrated in a recent study [ 11 ] and show a predominance of E. coli and Staphylococcus in intraabdominal swabs. DMBT1 addresses a critical factor in the pathogenesis of NEC.…”
Section: Discussionsupporting
confidence: 92%
“…The total intestinal DMBT1 expression level was slightly but not significantly higher in infants with PDA/CHD compared to infants without cardiac anomalies. This corresponds to the higher inflammation and supports the results of our own data indicating that infants with PDA/CHD had more frequently macroscopic intestinal necrosis and positive bacterial culture of intraoperative swabs compared to preterm infants without PDA/CHD [ 11 ]. Cellular hypoxia may also lead to higher DMBT1 expression in intestinal epithelium.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Next, we determined whether Hb level, r s SO 2 , and variability of r s SO 2 were associated with level of I-FABP, and whether Hb level and r s SO 2 measurements were interrelated, on several time points prior to transfusion using Spearman’s Correlation Test, in all infants irrespective of group assignment, and in cases and controls separately. Since was suggested that the blood flow in the intestines may be impaired in infants with a PDA, 34 , 35 we additionally calculated partial correlation coefficients to correct for the potential influence of a PDA. Finally, we performed linear regression analyses to determine the effect size of Hb level, r s SO 2 , and r s SO 2 variability on urinary I-FABP level closest to RBC transfusion.…”
Section: Methodsmentioning
confidence: 99%